Flocculation Behavior of Borax Clayey Tailings in Mono- and Dual- Flocculant Systems: Effect of Tailings Slurry Characteristics and polyDADMAC Type - Karapinar, Nuray (Global Journal of Earth Science and Engineering, 2019)
The effect of tailings slurry characteristics such as solid ratio and solid particle size both, in mono- and dualflocculant systems, were studied as well as the effect of POLYDADMAC type in dual-flocculant system. Oppositely charged flocculants, a polyacrylamide (PAM)-typed anionic and two poly diallyl-dimethyl-ammonium chloride(polyDADMAC)-typed cationic polymers, were employed for the flocculation. Tailings slurry samples were taken on different dates from the discharge point of Kırka Borax Concentrator. Flocculation performance was characterized by the initial settling rate as well as the residual turbidity of supernatant and the extent of sediment compaction. All tests were performed at the natural pH of the tailings slurry ( pH 9.4) at which borax buffered the suspension. The results showed that an increase in solid load of the tailings slurry results in a dramatic decrease in settling rate of flocculated tailings regardless of flocculant system employed. This can be attributed to the possible change in rheological property of the slurry due to the increasing clay content of the slurry with solid ratio. While the solid ratio has an influence on the settling rate of the flocculated tailings, the amount of slimes determines the optimum dosage of cationic flocculant to obtain clear supernatant in dual-flocculant system. When anionic and cationic flocculants were used in combination, the best synergy was achieved with low weight cationic flocculant. Increasing molecular weight of the cationic flocculant from low to medium resulted in two-fold increase in the required dosage to obtain the same flocculation performance. In dualflocculant system, optimum results were obtained by anionic and cationic flocculant combination at around 0.4 kg/ton and 0.8 kg/ton solid dosages, respectively, indicating 11.7 cm/min of settling rate and 85.7% of transmittance value.